Strategi Komunikasi Politik dalam Resolusi Konflik Pemindahan Ibu Kota Negara Indonesia: Pendekatan Konstruktif dan Kolaboratif - Hidayat, Rachmat; Rahmat Saleh; Herman Paninggiran; Yusnaini; Jamalullail (LPPM Stikosa - AWS, 2025)
The relocation of the capital city of Indonesia from Jakarta to East Kalimantan is a strategic policy that presents various challenges, including complex political conflicts. This conflict involves the rejection by indigenous communities regarding land rights, concerns about environmental impacts, and the lack of public participation in the decision-making process. This research aims to examine the role of communication in managing the political conflicts arising from this policy. Through the application of Conflict Theory by Littlejohn, Constructive Controversy by Peter T. Coleman, and the Theory of Cooperation and Competition by Morton Deutsch, this research analyzes the role of communication in alleviating conflicts, building cooperation, and achieving consensus among stakeholders. This research applies the Systematic Literature Review (SLR) method to identify studies related to political communication and conflict resolution in the context of public policy during the period 2022–2024. The research findings indicate that public resistance can be attributed to the inadequacy of inclusive narratives and the lack of participatory dialogue. A communication approach that prioritizes collaboration through constructive dialogue and narratives reflecting shared interests has the potential to transform destructive conflicts into more productive negotiation processes. The conclusion drawn from this study is a recommendation for the implementation of clearer communication strategies, involving all parties, and focusing on collaboration to create agreements among stakeholders.